„Katalog magii” Rudolfa i Długoszowy „Olimp”. Z dziejów synkretyzmu religijnego na ziemiach polskich w średniowieczu - Cetwiński, Marek (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2025)
The article analyses sources of information about the cultivation of rituals and beliefs considered by clerical writers to be “remains” of paganism by the common people in Poland in the 14th and 15th centuries. A detailed analysis of the content of these accounts indicates that the “pagans” (a term used by the sources to describe people who had been formally baptised) had adopted many themes inspired by content derived indirectly from Christianity and ancient culture. These influences are particularly evident in the spread of ancient magical practices. The local, non-Christian pantheon of deities described by chronicler Jan Długosz also indicates that religious beliefs drew on these inspirations. The arguments presented above are in favour of rejecting Brückner’s a priori views on the low credibility of Długosz’s account. However, Długosz committed an anachronism by transferring his contemporary phenomena to pre-Christian times. The sources collected indicate that “pagan” relics survived in Poland as long as until the 15th century.